HOLISTICS JOURNAL HOLISTICS JOURNAL HOSPITALITY AND LINGUISTICS: Using Reciprocal Teaching Method to Improve Female Students’ Reading Comprehension Achievement at SMA Negeri Tujuh Prabumulih - Leonardi Jaye (HOLISTICS, 2021)
Reading comprehension is a complex process that involves the combination of many competencies and abilities. In the context of EFL classrooms, the purpose of this study was to investigate the effect of reciprocal teaching on reading comprehension towards female students’ reading comprehension achievement. The method used was four comprehension strategies: predicting, questioning, clarifying, and summarizing, to help students monitor their development of reading comprehension by themselves. A pre-test post-test non-equivalent groups is used as the experimental design. The population of the present study is first-year students at SMA Negeri 7 Prabumulih during the academic year 2020-2021. The population is 60 female students as sample by using random sampling. Both students of the experimental and control groups were exposed to pre and post-tests. Using the t-test for two independent samples, it is found that there is a statistically significant difference in favour of the experimental group. The results also showed that female students preferred this method for teaching learning reading compared to the conventional one. Therefore, teachers are suggested to consider using this method for teaching reading that instils the students on how to apply the four comprehension strategies used in reading.